Age‐dependent impairment of glucose tolerance in the 3xTg‐AD mouse model of Alzheimer's disease. Issue 10 (24th June 2015) - Vandal, Milene; White, Phillip J.; Chevrier, Geneviève; Tremblay, Cyntia; St.‐Amour, Isabelle; Planel, Emmanuel; Marette, Andre; Calon, Frederic
ABSTRACT: Alzheimer's disease (AD) has been associated with type II diabetes (T2D) and obesity in several epidemiologic studies. To determine whether AD neuropathology can cause peripheral metabolic impairments, we investigated metabolic parameters in the triple‐transgenic (3xTg)‐AD mouse model of AD, compared with those in nontransgenic (non‐Tg) controls, at 6, 8, and 14 mo of age. We found a more pronounced cortical Aβ accumulation (2‐and 3.5‐fold increase in Aβ42 in the soluble and insoluble protein fractions, respectively) in female 3xTg‐AD mice than in the males. Furthermore, female 3xTg‐AD mice displayed a significant deterioration in glucose tolerance (AUC, +118% vs. non‐Tg mice at 14 mo). Fasting plasma insulin levels rose 2.5‐fold from 6 to 14 mo of age in female 3xTg‐AD mice. Glucose intolerance and cortical amyloid pathology worsened with age, and both were more pronounced in the females. Pancreatic amyloidopathy was revealed and could underlie the observed deficit in glycemic response in 3xTg‐AD mice. The present results suggest that AD‐like neuropathology extends to the pancreas in the 3xTg‐AD mouse, leading to glucose intolerance and contributing to a pathologic self‐amplifying loop between AD and T2D.—Vandal, M., White, P. J., Chevrier, G., Tremblay, C., St‐Amour, I., Planel, E., Marette, A., Calon, F. Age‐dependent impairment of glucose tolerance in the 3xTg‐AD mouse model of Alzheimer's disease. FASEB J. 29, 4273‐4284 (2015). www.fasebj.org